2007
DOI: 10.1111/j.1572-0241.2006.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopist Can Be More Powerful than Age and Male Gender in Predicting Adenoma Detection at Colonoscopy

Abstract: Who performs the procedure can be more important than age and gender in predicting adenomas at colonoscopy. Our results underscore the need to measure adenoma detection rates in the continuous quality improvement process and to report them to endoscopists. Additional data are needed to determine whether corrective measures can reduce variation in adenoma detection rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
245
4
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 379 publications
(272 citation statements)
references
References 29 publications
13
245
4
10
Order By: Relevance
“…Increases in ADR are inversely correlated with CRC mortality and post colonoscopy CRC rates (4,14,(16)(17)(18)(19). These findings have led the American College of Gastroenterology Task Force on Quality in Endoscopy and the American Society for Gastrointestinal Endoscopy to update their ADR targets to >30% for men and >20% for women (20).…”
Section: Discussionmentioning
confidence: 97%
“…Increases in ADR are inversely correlated with CRC mortality and post colonoscopy CRC rates (4,14,(16)(17)(18)(19). These findings have led the American College of Gastroenterology Task Force on Quality in Endoscopy and the American Society for Gastrointestinal Endoscopy to update their ADR targets to >30% for men and >20% for women (20).…”
Section: Discussionmentioning
confidence: 97%
“…The adenoma detection rates of endoscopists, including those within groups of gastroenterologists, vary widely [35][36][37][38] . No substantial study examining adenoma detection rates has ever shown a less than 2.5 fold difference between the highest and lowest detectors in the same group, and this variation has ranged to up to 8 fold [35][36][37][38] .…”
Section: Case-control Studies Of Colonoscopy On Right-sided Incidencementioning
confidence: 99%
“…Numerous studies have demonstrated marked (twofold to sixfold) variability in ADRs among endoscopists working in the same endoscopy unit [4]. Although some of this variability might be due to patient factors such as age, gender, or adequacy of bowel preparation, individual endoscopists appear to be the single most predictive factor in adenoma detection [7], implying that the efficacy of colonoscopy is highly dependent on the individual skill of the endoscopist. To compound matters, Brenner [8] and Lakoff [9] presented data from Germany and Canada that showed that while colonoscopy does decrease the rate of distal CRCs by approximately 67-79%, it was not at all protective for proximal colon cancers, suggesting that there is a substantial need for improvement in colonoscopy quality by all endoscopists.…”
mentioning
confidence: 99%
“…Nonetheless, there is now substantial data, including from the US that colonoscopy quality varies by specialty training in both a statistically and clinically meaningful manner with gastroenterologists typically having the lowest overall interval CRC rates. This issue has been discussed repeatedly [4,[6][7][8][9][10][11][12][13][14][15]; it is time for the medical community to act on this information.…”
mentioning
confidence: 99%